Antibacterial and cytotoxic activity from the extract and fractions of a marine derived bacterium from the Streptomyces genus - Malagon Aviles, O. (2015)
Context: Marine natural products are a rich source of potent, selective, and structurally novel compounds. Marine bacteria are considered the most promising source of biologically active compounds which can be applied to treat a wide range of diseases. Objective: The current study was designed to establish the bases for a future marine exploration in the Ecuadorian coast based on the molecular identification of a marine bacterium and its potential use as an antibacterial or cytotoxic compounds source. Materials and methods: Isolation and characterization of the marine bacterium were carried out through microbiological methods from desiccated sediment. Molecular identification was made by means of 16S rDNA analysis. MIC was measured by the microdilution broth method against six pathogenic bacteria: two Gram positive and four Gram negative strains. Cytotoxicity was evaluated by Crystal violet assay against breast adenocarcinoma (MCF7) and ductal carcinoma (T47D and ZR-75-30). Results: Our present study has shown that EtOAc extract and fraction A1 obtained from marine Streptomyces sp. revealed the maximal antibacterial and cytotoxic activity. Enterococcus faecalis was found to be more sensitive strain (MIC 0.78 ?g/ml) than the other five bacteria tested. ZR-75-30 and T47D cell lines were found to be more sensitive (IC50 value, 31.88 0.05 and 68.35 0.12 ?g/ml) than adenocarcinoma MCF7 (IC50 value was 83.65 0.06 ?g/ml). Discussion and conclusion: The results obtained herein indicate that EtOAc extract of Streptomyces sp. has shown a strong antibacterial activity as well as moderate cytotoxic activity which make it a good candidate for metabolite isolation. © 2015 Informa Healthcare USA, Inc.